SmpB and tmRNA Orchestrate Purine Pathway for the Trimethoprim Resistance in Aeromonas veronii - Wang, Dan; Li, Hong; Khan, Wasi Ullah; Ma, Xiang; Tang, Hongqian; Tang, Yanqiong; Huang, Dongyi; Liu, Zhu (Frontiers in Cellular and Infection Microbiology, 2020)
Small protein B(SmpB) cooperates with transfer-messenger RNA (tmRNA) for trans-translation to ensure the quality control of protein synthesis in prokaryotes. Furthermore, they regulate cell metabolism separately. According to research, SmpB functions as a transcription factor, and tmRNA acts as a small RNA. Purine pathway has been reported to be related to trimethoprim resistance, including hypoxanthine synthesis, adenosine metabolism and guanosine metabolism. Another reason of drug tolerance is the efflux pump of the bacterium. In transcriptomic data, it was showed that the expression of some related enzymes in adenosine metabolism were raised significantly in smpB deletion strain than that of wildtype, which led to the differential trimethoprim resistance of Aeromonas veronii (A. veronii). Furthermore, the metabolic products of adenosine AMP, cAMP, and deoxyadenosine were accumulated significantly. However, the expressions of the enzymes related to hypoxanthine synthesis and guanosine metabolism were elevated significantly in ΔtmRNA, which eventually caused an augmented metabolic product xanthine. In addition, the deletion of tmRNA also affected the significant downregulations of efflux pump acrA/acrB. The minimal inhibitory concentrations (MIC) were overall decreased after the trimethoprim treatment to the wild type, ∆smpB and ∆tmRNA. And the difference in sensitivity between ∆smpB and ∆tmRNA was evident. The MIC of ∆smpB was descended significantly than those of wild type and ∆tmRNA in M9 medium supplemented with 1 mM adenosine, illustrating that the adenosine metabolism pathway was principally influenced by SmpB. Likewise, the strain ∆tmRNA conferred more sensitivity than wild type and ∆smpB in M9 medium supplemented with 1mM guanosine. By overexpressing avrA/acrB, the tolerance to trimethoprim was partially recovered in ∆tmRNA. These results revealed that SmpB and tmRNA acted on different branches in purine metabolism, conferring the diverse trimethoprim resistance to A. veronii. This study suggests that the trans-translation system might be an effective target in clinical treatment of A. veronii and other multi-antibiotic resistance bacteria with trimethoprim.